Kinetic Parameters from TG Analysis of Cobalt (II) Complex of the Schiff base Derived From Salicylaldehyde and Thiocarbohydrazide - Verma, U.N. (Asian Journal of Chemistry, 2010)
Cobalt(II) chloride forms a 1: 1 complex with Schiff base ofsalicyldehyde and thiocarbohydrazide. Kinetic parameters like apparentactivation energy, frequency factor, activation entropy and apparent orderof reaction of complex have been determined employing Freeman-Carroll,Fuoss et al., Coats-Redfern, Karkhanawala-Dharwadker and Doyle methodsas modified by Zsako using non-isothermal TG curves. These valuesare in good agreement with each other. The complex decomposes regularlywithout any distinguishable rest with random nucleation mechanism.